Ciências sociais e ideologia : uma abordagem crítica da teoria social clássica na perspectiva lukacsiana - Silva, Fabricio Tavares da (2011)
This research is the main problem the complex relationship between science, especially the social sciences, and the complex of ideology from the perspective of historical ontology and György Lukács. Take a few significant works of the founders of Classical Social Theory (Emile Durkheim and Max Weber) as objects of our analysis. In addressing the problem of ideology in social science from the approach Lukacsian, uses critical reading to grasp the immanent connections conceptual and analytical, in the authors\' theories and propositions in question. The study first presents the fundamental elements of the perspective adopted, as well as the categories of Ideology and Science in Lukacsian approach. It starts with the notion that work is the foundation of social being, and that their development will gradually produce new social complexes. The problems of science, its emergence in social being, their complexity and refinement, many of their problems and issues are considered as moments of a procedural development and contradictory, historically and socially determined, whose dynamic is intertwined with the previous work. With the development of capitalism, this relationship becomes stronger, boosting the expansion of capital, while doing a science activity more elaborate, as their horizons are expanded in an increasing manner. It is still considered the everyday, as the space between the actions of individuals\' here and now, and its objectivations in science. The main methodological boundaries proposed by Emile Durkheim, present in two of his works: From the Division of Labor and Social Suicide, are examined. The main themes and concepts of Max Weber are reviewed from the theoretical framework above. Proposals for a \"value-free science\" of Weber, a science and devoid of \"preconceived notions\" of Durkheim, are analyzed in order to understand how their significant works equate the problem of ideology.